Question

Laplace Transform of y"+3y'+2y=0 , y(2)=1 , y'(0)=0

Answer #1

Use
Laplace transform to solve IVP
2y”+2y’+y=2t , y(0)=1 , y’(0)=-1

Given the second order initial value problem
y′′−3y′=12δ(t−2), y(0)=0, y′(0)=3y″−3y′=12δ(t−2), y(0)=0, y′(0)=3Let
Y(s)Y(s) denote the Laplace transform of yy. Then
Y(s)=Y(s)= .
Taking the inverse Laplace transform we obtain
y(t)=

solve using the laplace transform y''-2y'+y=e^-t , y(0)=0 ,
y'(0)=1

y^''-y^'-2y= e^t , y(0)=0 and y^'(0)=1
Solve by using laplace transform

Use
the Laplace transform to solve:
y’’ + 2y’ + y = e^(2t); y(0) = 0, y’(0) = 0.

y'-2y = 8sin(2t) , y(0) = -4
Use Laplace Transform

Solve the initial value problem using
Laplace transform theory.
y”-2y’+10y=24t,
y(0)=0,
y'(0)= -1

Solve y'-3y=2e^t y(0)=e^3-e using Laplace transform.

Use Laplace transform to solve the following initial value
problem: y '' − 2y '+ 2y = e −t , y(0) = 0 and y ' (0) =
1
differential eq

Solve the following initial value problem using Laplace
transform
y"+2y'+y=4cos(2t) When y(0)=0 y'(0)=2
Thankyou

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 43 seconds ago

asked 10 minutes ago

asked 18 minutes ago

asked 20 minutes ago

asked 21 minutes ago

asked 36 minutes ago

asked 43 minutes ago

asked 45 minutes ago

asked 48 minutes ago

asked 48 minutes ago

asked 49 minutes ago

asked 1 hour ago